Central venous catheter malposition into axillary vein - Nazir, Ovais; Wani, Mushtaq A.; Jain, Ashu Kumar; Sharma, Tarun (International Journal of Research in Medical Sciences, 2017)
Placement of CVC can lead to complications such as, malposition of the catheter and complications relating to perforation and/or injury of nearby blood vessels and structures. We present a case report is about malposition of central venous catheter (CVC) from right internal jugular vein (IJV) into right subclavian and axillary vein. It is advisable to check free venous outflow in all the ports of CVC, central venous waveform should obtained with transducer in place and following placement of CVC catheter, chest radiograph should be completed to confirm the position.